Post corona : from crisis to opportunity - Galloway, Scott, 1964- (Portfolio Penguin, 2020)
"New York Times bestselling author Scott Galloway argues, the pandemic has not been a change agent so much as an accelerant of trends already well underway. In Post Corona, he outlines the contours of the crisis and the opportunities that lie ahead. Some businesses, like the powerful tech monopolies, will thrive as a result of the disruption. Other industries, like higher education, will struggle to maintain a value proposition that no longer makes sense when we can't stand shoulder to shoulder. And the pandemic has accelerated deeper trends in government and society, exposing a widening gap between our vision of America as a land of opportunity, and the troubling realities of our declining wellbeing."-- Provided by publisher.